Formalisation as a judicial claim - Lorena Poblete (Cidades, Comunidades e Território)
In Argentina, the majority of domestic workers are not registered. The combination of a lack of regulatory frameworks, limited inspection capabilities on the part of the state, and the culturally entrenched notion of domestic work as “servitude” and “help” has made informality the rule for paid domestic workers. Thus, formalisation is considered fundamental for the recognition of the social and labour rights, at both the policy and individual levels. The latter is evident in the process of labour disputes resolution established by the Domestic Work Tribunal in Buenos Aires. As a consequence, this article seeks to understand how the demand for formalisation appears at the centre of disputes over the recognition of rights at the Domestic Work Tribunal, becoming a judicial claim. How is formalisation used in the context of an individual labour dispute at the tribunal?This paper, which is divided into two sections, draws on a study of the legal framework for paid domestic work, a quantitative and qualitative analysis of 156 judicial files and 1,000 rulings, and four months of ethnographic fieldwork. The first section analyses the way in which the process of formalisation is discussed, conceived, and implemented at the international and national level, and the way it is appropriated by employers and domestic workers. The second focuses on the dispute resolution process in which the meaning of formalisation changes according to the diverse actors involved.